COMMUNITY CENTER GENERASI BARU INDONESIA (GENBI) KALIMANTAN SELATAN DI KOTA BANJARBARU - Siti Maulida; Dahliani Dahliani (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
GenBI South Kalimantan is a community of Bank Indonesia scholarship recipients actively engaged in various work programs, ranging from community service to skill enhancement, and fostering close collaborations with various parties. With the potential increase in the reach of Bank Indonesia scholarship recipients in the South Kalimantan region, this community faces limited adequate facilities to support its high intensity of activities. Therefore, a Community Center in Banjarbaru City is designed to accommodate the collaborative activities of the GenBI South Kalimantan community with flexible spatial functionality. To achieve this goal, a space flexibility method is utilized by applying three main strategies: expandability, convertibility, and versatility. The implementation of these strategies forms the basis of the Flex Collaborative Space concept, which guides the formation of spatial zones, activity zones, and inter-room relationships, allowing the space to adapt to changing activities within the Community Center. The design outcome is a Community Center with communal spaces equipped with flexible elements such as open circulation, visual transparency, modular furniture, and non-fixed components. Thus, this rectangular-shaped building, modified through addition techniques and mass breaking (inner court massing), has the potential to become a functional and adaptive collaborative hub for GenBI and the surrounding community.